Aluminium‐ and gallium‐doped homoepitaxial ZnO thin films: Strain‐engineering and electrical performance. Issue 7 (17th April 2015) - Lorenz, Michael; Weiss, Tobias; Schmidt, Florian; von Wenckstern, Holger; Grundmann, Marius
Abstract Aluminium‐ and gallium‐doped ZnO thin films with nominal source target compositions of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkx82" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.1</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkx9m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1wt%</alternatives> were grown homoepitaxially and in‐plane lattice matched on c‐plane ZnO <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkx6z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(00.1‾)</alternatives> single crystalline substrates. In dependence on dopant concentration and oxygen partial pressure during growth we found compressive or tensile out‐of‐plane epitaxial strain up to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9pkx7h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.1%</alternatives>. Electrical investigations showed that the conductivity of the substrates alters transport properties at room temperature. Correct interpretation requires variable temperature Hall effect measurements. These reveal, that besides the contributions of the substrate and the deposited thin film an additional conduction channel, likely located at the surface of the samples must be considered to explain and model the temperature dependence of the free electron concentration and their mobility.